CD24, A Review of its Role in Tumor Diagnosis, Progression and Therapy - Ni, Yang-Hong; Zhao, Xia; Wang, Wei (Current Gene Therapy, 2020)
CD24, is a mucin-like GPI-anchored molecules. By immunohistochemistry, it is widely detected in many solid tumors, such as breast cancers, genital system cancers, digestive system cancers, neural system cancers and so on. The functional roles of CD24 are either fulfilled by combination with ligands or participate in signal transduction, which mediate the initiation and progression of neoplasms. However, the character of CD24 remains to be intriguing because there are still opposite voices about the impact of CD24 on tumors. In preclinical studies, CD24 target therapies, including monoclonal antibodies, target silencing by RNA interference and immunotherapy, have shown us brighten futures on the anti-tumor application. Nevertheless, evidences based on clinical studies are urgently needed. Here, with expectancy to spark new ideas, we summarize the relevant studies about CD24 from a tumor perspective.
Keywords: lymphocytes